2006
DOI: 10.1099/jmm.0.46512-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic bacteria in 118 patients with deep-space head and neck infections from the University Hospital of Maxillofacial Surgery, Sofia, Bulgaria

Abstract: Anaerobic bacteria in 118 patients with deepspace head and neck infections from the University Hospital of Maxillofacial Surgery, Sofia, Bulgaria The aim of this study was to assess the incidence and susceptibility to antibacterial agents of anaerobic strains in 118 patients with head and neck abscesses (31) and cellulitis (87).Odontogenic infection was the most common identified source, occurring in 73 (77?7 %) of 94 patients. The incidence of anaerobes in abscesses and cellulitis was 71 and 75?9 %, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 17 publications
2
29
0
1
Order By: Relevance
“…Pathogens that cause DNI show various levels of antibiotic resistance--thus, infection may not respond to therapy, and complications may occur. Boyanevo et al [12] reported 74% anaerobic reproduction and 2.5-58.3% resistance to clindamycin and metronidazole in these strains. Considering these high resistance rates, antibiotic regimens must be updated in the near future.…”
Section: Roentgenmentioning
confidence: 84%
“…Pathogens that cause DNI show various levels of antibiotic resistance--thus, infection may not respond to therapy, and complications may occur. Boyanevo et al [12] reported 74% anaerobic reproduction and 2.5-58.3% resistance to clindamycin and metronidazole in these strains. Considering these high resistance rates, antibiotic regimens must be updated in the near future.…”
Section: Roentgenmentioning
confidence: 84%
“…In the pre‐antibiotic era, most DNI resulted from pharyngotonsillar infections. Contemporary studies described dental infection as the most commonly identified source of DNI . Dental infection is typically associated with higher incidence of anaerobic bacteria compared to infections of non‐dental aetiology …”
Section: Discussionmentioning
confidence: 99%
“…Among the agents used against obligate anaerobic isolates, Chloramphenicol and Clindamycin were effective (62.5%) with an unexpected high resistance to Metronidazole (75%). A lower resistance rate to Clindamycin than metronidazole among Gram-negative anaerobes was also found by Boyanova et al (2006) (25) . However, metronidazole was described by Saini et al (2003) (21) as the drug of choice against anaerobes.…”
Section: Discussionmentioning
confidence: 82%